2013
DOI: 10.1089/ast.2012.0887
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Simulation of Evaporation-Driven Silica Sinter Formation and Microbial Silicification in Hot Spring Systems

Abstract: Evaporation of silica-rich geothermal waters is one of the main abiotic drivers of the formation of silica sinters around hot springs. An important role in sinter structural development is also played by the indigenous microbial communities, which are fossilized and eventually encased in the silica matrix. The combination of these two factors results in a wide variety of sinter structures and fabrics. Despite this, no previous experimental fossilization studies have focused on evaporative-driven silica precipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(26 citation statements)
references
References 59 publications
(132 reference statements)
1
25
0
Order By: Relevance
“…Silicification of organic remains involves the bonding of silicic acid to organic cell walls or envelopes, ensuring long-term stability (e.g., Knoll, 1985). Experiments have confirmed that diverse archaeal and bacterial extremophiles and even viruses silicify readily in silica saturated solutions, with minimal dependence on cell/substrate type, pH, or salinity (Orange et al, 2009(Orange et al, , 2013(Orange et al, , 2014Westall et al, 1995;Westall, 1997). Such results suggest that silicification could outpace cell lysis and degradative processes in brines on early Mars (e.g., Harrison et al, 2016;Toporski et al, 2002;Yee et al, 2003).…”
Section: Hydrothermal Silicamentioning
confidence: 99%
“…Silicification of organic remains involves the bonding of silicic acid to organic cell walls or envelopes, ensuring long-term stability (e.g., Knoll, 1985). Experiments have confirmed that diverse archaeal and bacterial extremophiles and even viruses silicify readily in silica saturated solutions, with minimal dependence on cell/substrate type, pH, or salinity (Orange et al, 2009(Orange et al, , 2013(Orange et al, , 2014Westall et al, 1995;Westall, 1997). Such results suggest that silicification could outpace cell lysis and degradative processes in brines on early Mars (e.g., Harrison et al, 2016;Toporski et al, 2002;Yee et al, 2003).…”
Section: Hydrothermal Silicamentioning
confidence: 99%
“…Hence, the high degrees of supersaturation would predict homogeneous nucleation in the water and deposition of pre-constituted particles (Campbell et al, 2001;Lynne and Campbell, 2004;Orange et al, 2013).…”
Section: Silica Precipitation and Nucleationmentioning
confidence: 99%
“…Most sinter deposits are produced from near-neutral pH alkali chloride springs, with accumulations that are centimeters to meters thick, but acid-sulfate-chloride springs with pH as low as 2.1 are also known to produce sinter deposits (Schinteie et al, 2007). Because hot springs commonly host extensive microbial communities, the role of microbes in facilitating silica precipitation has long been debated (e.g., Weed, 1889;Allen, 1934;White et al, 1956;Walter et al, 1972) and continues to be investigated (e.g., personal communication; Tobler et al, 2008;Orange et al, 2013;Murphy et al, personal communication). The potential for sinter deposits to entomb and preserve biomaterials and textures over geological timescales is well documented (e.g., Campbell et al, 2019;Campbell et al, 2001;Djokic et al, 2017;Guido et al, 2010;Rice et al, 1995;Teece et al, 2020 in this issue;Walter et al, 1996;White et al, 1989), which is a primary reason that they are a favored target in the search for ancient life on Mars (e.g., Walter and Des Marais, 1993;Farmer and Des Marais, 1999;Cady et al, 2018).…”
Section: Introductionmentioning
confidence: 99%